Evaluation of different mechanical cleaning protocols associated with 2.5% sodium hypochlorite in the removal of residues from the post space - Vitória, Matheus Sousa [UNESP]; De Almeida, Eran Nair Mesquita [UNESP]; Barros, Antonia Patricia Oliveira [UNESP]; De Oliveira, Eliane Cristina Gulin [UNESP]; Costa, Joatan Lucas de Sousa Gomes [UNESP]; Dantas, Andrea Abi Rached [UNESP]; Kuga, Milton Carlos [UNESP] (Wolters Kluwer, 2024)
Aims: This study evaluated the effectiveness of different mechanical protocols using rotary brush (RB), ultrasonic tip, and oscillatory system (OS) associated with 2.5% sodium hypochlorite (NaOCl) in the removal of residues and dentin permeability in the cervical and apical segments of the post space. Settings and Design: Experimental in vitro study. Methods: Forty roots from human first molars were prepared and divided into four groups according to the cleaning protocols: Control (CO), NaOCl 2.5% conventional irrigation with a syringe; RB associated with NaOCl 2.5%; ultrasonic tip (US) associated with NaOCl 2.5%; OS associated with NaOCl 2.5%. Statistical Analysis Used: The persistence of residues was evaluated by scanning electron microscopy and data submitted to Kruskal–Wallis and Dunn tests, and dentin permeability evaluated by confocal microscopy and date submitted to ANOVA one‑way and Tukey’s tests (P = 0.05). Results: There were no differences in residue cleaning among the CO, RB, US, and OS groups, regardless of the analyzed root segment (P > 0.05). When comparing groups, dentin permeability in the CO group was significantly lower in the cervical segment (P < 0.05). Conclusions: The OS group promoted the highest permeability value in the apical segment. RB, US, and OS are similar in removing residues from the post space. However, OS results in higher dentin permeability in the apical segment.
Keywords: Cleaning; dentin permeability; post space; protocols; ultrasound